Konsep Pendidikan Islam dalam Perspektif Muhammad Fethulah Gulen - Mubaidi Sulaiman (Sekolah TinggiAgama Islam Negeri (STAIN) Kediri, 2016)
The role of education is very important in life. Education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learners are actively developing the potential for him to have the spiritual power of religion, self-control, personality, intelligence, character, and skills that are needed by themselves, society, nation and state. One of the leading figures in education from Turky is Fethullah Gülen with his Hizmet, in which science and religion are to be integrated for all mankind regardless of race, ethnicity, religion and culture. His thoughts are often referred by many thinkers in contemporary Islamic education as he is known as progressive thinker.